2016
DOI: 10.1038/oncsis.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 codon72 Arg>Pro polymorphism with susceptibility to nasopharyngeal carcinoma: evidence from a case–control study and meta-analysis

Abstract: Tumor suppressor p53 is a critical player in the fight against cancer as it controls the cell cycle check point, apoptotic pathways and genomic stability. It is known to be the most frequently mutated gene in a wide variety of human cancers. Single-nucleotide polymorphism of p53 at codon72 leading to substitution of proline (Pro) in place of arginine (Arg) has been identified as a risk factor for development of many cancers, including nasopharyngeal carcinoma (NPC). However, the association of this polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Thus, this is the first report regarding the role of the TP53 genetic variant in gallbladder cancer risk in Indians. In contrast, Sahu (2016) reported that both allele frequency and genotype distribution of the TP53 polymorphism are associated with an increased risk of nasopharyngeal carcinoma in a meta-analysis. Our findings that the CC genotype is associated with an increased risk of gallbladder cancer should be examined in additional studies with a larger sample size, a meta-analysis, or a systematic review.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, this is the first report regarding the role of the TP53 genetic variant in gallbladder cancer risk in Indians. In contrast, Sahu (2016) reported that both allele frequency and genotype distribution of the TP53 polymorphism are associated with an increased risk of nasopharyngeal carcinoma in a meta-analysis. Our findings that the CC genotype is associated with an increased risk of gallbladder cancer should be examined in additional studies with a larger sample size, a meta-analysis, or a systematic review.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, this high incidence of NPC in specific ethnic groups indicates genetic factors controlling the disease. A number of reports have suggested the role of various genetic factors in association with NPC; particularly, polymorphisms in the histocompatibility locus antigens (HLA), cytochrome P450 2E1 (CYP2 E1), alteration of p53 codon 72 Arg>Pro, and some signaling pathways (82)(83)(84)(85)(86)(87)(88)(89)(90)(91). It has been reported that human 8-oxoguanine DNA glycosylase 1 (hOGG1) gene and human MutY glycosylase homologue (hMUTYH) gene polymorphism is associated to the risk of NPC mainly among women in Chinese population (92).…”
Section: Genetic Factors Render the Body Susceptible To The Diseasementioning
confidence: 99%
“…Substitution of proline (Pro) in place of arginine (Arg) at codon 72 of the p53 product plays a role in disease susceptibility. Individuals with Arg/Arg genotype have a lower risk of getting NPC compared to the individuals with Arg/ Pro genotype; and those with Pro/Pro genotype have a much higher risk of acquiring NPC (90). Recently, codon 72 Arg>Pro polymorphism and the risk of NPC has been reported in Northestern India.…”
Section: Tumor Suppressors and Oncogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Finally, various host genetic factors have been reported to be associated with NPC, particularly polymorphisms in the class I histocompatibility locus antigens (HLA class I), cytochrome P450 2E1 (CYP2 E1), alteration of p53 codon 72 Arg>Pro and some signalling pathways. [15][16][17][18][19][20][21] After initial infection with EBV, antigenic presentations of EBV-derived peptides are involved in the pathogenesis of the virus, eventually leading to cancers like NPC. HLA genes express various proteins of the immune system and help it to process and present foreign antigens, thereby making those antigens vulnerable to immune lysis.…”
Section: Introductionmentioning
confidence: 99%